Proceedings of the 6th International Conference on Predictive Models in Software Engineering 2010
DOI: 10.1145/1868328.1868357
|View full text |Cite
|
Sign up to set email alerts
|

Programmer-based fault prediction

Abstract: Background: Previous research has provided evidence that a combination of static code metrics and software history metrics can be used to predict with surprising success which files in the next release of a large system will have the largest numbers of defects. In contrast, very little research exists to indicate whether information about individual developers can profitably be used to improve predictions.Aims: We investigate whether files in a large system that are modified by an individual developer consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 33 publications
0
52
0
Order By: Relevance
“…Different developers have different experience levels, different coding styles, and different commit patterns, resulting in different buggy change patterns [11]. Figure 2 shows differences in buggy change patterns of four prolific Linux kernel developers in the mainline repository from 2005 to 2010.…”
Section: Personalized Change Classification (Pcc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Different developers have different experience levels, different coding styles, and different commit patterns, resulting in different buggy change patterns [11]. Figure 2 shows differences in buggy change patterns of four prolific Linux kernel developers in the mainline repository from 2005 to 2010.…”
Section: Personalized Change Classification (Pcc)mentioning
confidence: 99%
“…Recently, Shivaji et al [48] improve the work above by applying feature selection algorithms. Ostrand et al [11] use negative binomial regression as the classifier, and various metadata and developer-specific metrics as features to predict defects. Rahman et al [16] compare the effect of code metrics and process metrics.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other publications of Khoshgoftaar and Seliya from 2004 [15] and 2005 [16] continued with the previous concept and focused on commercial data analysis, but were not applied to a real-world environment. A similar approach can be found in publications by Ostrand and Weyuker [29], Ostrand et al [31], Tosun et al [45], Turhan et al [47,48]. Examples of industrial applications of information gathered by using defect prediction can be found in publications by Wong et al [50], Succi et al [41] and Kläs et al [17].…”
Section: Related Workmentioning
confidence: 84%
“…detected no significant contribution of this kind of developer information to the defect prediction performance. Following this research, the authors later analyzed the effectiveness of individual developer performance on the defect prediction performance and found no evidence of a significant improvement in the defect prediction performance either [39].…”
Section: People Related Metrics In Software Defect Predictionmentioning
confidence: 99%